Clinicopathological Analysis of 34 Cases of Primary Antineutrophil Cytoplasmic Antibody-Associated Vasculitis in Chinese Children - Jingyi Wu; Yuxin Pei; Liping Rong; Hongjie Zhuang; Shuhan Zeng; Lizhi Chen; Xiaoyun Jiang (Frontiers Media S.A., 2021)
Background: This study aimed to summarize the clinicopathological features and prognostic risk factors of primary antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) in children.Methods: Clinical and prognostic data for children admitted to our center with AAV between September 2003 and September 2020 were studied retrospectively. The incidence and risk factors of end-stage renal disease (ESRD) were calculated and analyzed.Results: Thirty-four children were enrolled; 28 were female, with a median onset age of 10 years. Except for one case negative for ANCA, the other 33 patients were diagnosed with microscopic polyangiitis (MPA). The most frequently involved organ was the kidney (100.0%), followed by the lungs (58.8%) and heart (50.0%). Twenty children (58.8%) progressed to ESRD with a median course of 3 months, and they were more likely to present respiratory and cardiovascular system involvement than were the non-ESRD group (P < 0.05). Patients in the ESRD group also had a higher serum creatinine level, 24-h protein excretion, Pediatric Vasculitis Activity Score (PVAS), and a lower level of estimated glomerular filtration rate (eGFR), hemoglobin, and complement C3 than had those in the non-ESRD group (P < 0.05). The main pathological manifestations were crescentic and sclerotic classes in the ESRD group and focal class in the non-ESRD group. After 6 months of induction therapy, 90.0% of cases achieved complete or partial remission. The multivariate logistic regression model showed that baseline eGFR < 60 ml/min/1.73 m2 was an independent risk factor for progressing to ESRD (OR = 0.016, 95% CI = 0.001~0.412, P = 0.012).Conclusions: AAV in children usually occurs in teenage girls, and the most commonly involved organ is the kidney, of which hematuria is the most common symptom, followed by proteinuria, abnormal renal function (eGFR < 90 ml/min/1.73 m2), etc. The primary type of AAV is MPA. Nearly 60% of patients progressed to ESRD with a median course of 3 months. Baseline eGFR < 60 ml/min/1.73 m2 is an independent risk factor for ESRD progression in AAV children.